Integrasi Aplikasi Let’s Read dalam Model RADEC untuk Meningkatkan Kemampuan Membaca Pemahaman Di Sekolah Dasar - Feby Inggriyani (Journal Of Human And Education (JAHE), 2026)
Reading comprehension remains a challenge in primary school education. Teacher-centered instructional methods, limited use of digital learning resources, and a lack of diversity in reading materials can hinder student engagement with texts. This study examines the implementation of the "Let’s Read" application integrated with the RADEC (Read-Answer-Discuss-Explain-Create) model for teaching reading comprehension to fourth-grade primary school students. A quantitative approach using a quasi-experimental design was employed with 52 students at an A-accredited primary school in Bandung Regency. Students were divided into an experimental group receiving RADEC instruction supported by "Let’s Read" and a control group receiving conventional instruction. Reading comprehension skills were measured using 32 multiple-choice questions that had undergone instrument quality testing. Data were analyzed using the Shapiro-Wilk test, homogeneity test, Independent Samples t-Test, and N-Gain analysis. The results showed a significant difference in post-test scores between the two groups, with a Sig. (2-tailed) value of 0.000. The experimental group achieved a mean score of 87.77, surpassing the control group's mean of 76.58. N-Gain calculations revealed an improvement of 30% in the experimental group and 17% in the control group, with both falling into the "moderate" category. Beyond academic achievement, teacher and student engagement during instruction was also higher in the experimental group. These findings indicate that integrating "Let’s Read" into RADEC-based instruction has the potential to foster a more active reading experience while supporting the development of reading comprehension skills among primary school students.